Performance of crosslinked bentonite-biocarbon electrodes for chromium mitigation through electrosorption - Ganesan, Vigneshhwaran; Kadhar Mohamed, Meera Sheriffa Begum (Separation science and technology, 2025)
Electrosorption has emerged as an energy-efficient technology for water deionization, yet high electrode costs limit its industrial adoption. The present study introduces a sustainable, cost-effective electrode design by crosslinking bentonite - a natural, stable clay mineral - with rice straw-derived biocarbon (ZC-B) to enhance chromium (Cr(VI)) removal from wastewater. The ZC-B electrodes exhibited a high specific surface area (580 m 2 /g), mesoporous structure, and significant specific capacitance (~68 F/g), optimized for Cr(VI) removal. Electrosorption tests demonstrated remarkable efficacy, achieving 99.57% Cr(VI) removal at 25 ppm and 90.02% at 250 ppm, with electrosorption capacities of 4.92 mg/g and 52.73 mg/g. Real-world trials on chrome plating effluent confirmed the ZC-B electrode's potential for industrial-scale Cr(VI) remediation, adhering to disposal standards. This work establishes bentonite-modified biocarbon as a promising, eco-efficient solution for heavy metal removal through electrosorption.